AUSTRALIA’S ROLE IN INDONESIA'S INFRASTRUCTURE DEVELOPMENT THROUGH KIAT 2017-2019 - Marthania Rizqy Amalia (UIR Press, 2020)
Australia has a big contribution in Indonesia’s infrastructure development, one of that is through the Indonesia Australia Infrastructure Partnership (KIAT) program, which was established in 2017. The KIAT program is implemented as an effort to boost Indonesia's economic growth by providing technical assistance to improve policies, planning and infrastructure provision. This study aimed to find out how the role, impact and interests of Australia in the KIAT program especially in 2017-2019. To analyze this program the writer uses the theory of Neoliberalism. With the theory of neoliberalism it can be seen that in its implementation KIAT not only involves the central government but also many private parties which show that the main actors of international relations are not only the state but other parties can also play an active role. In addition, both Indonesia and Australia try to maximize the absolute gain. In this project Australia has provided funds of AUD 146.2 million for the 2017-2021 period. Although Australia is a party that provides several budgets, Australia also can achieve its national interest from this partnership, especially in economic terms. Besides, Indonesia can also achieve its national interest because this partnership can accelerate economic growth through improved access to infrastructure.